PENGARUH PEMBERIAN CAMPURAN CAIRAN REBUSAN KAYU SECANG (CAESALPIA SAPPAN L.) DAN DAUN LIDAH BUAYA (ALOE VERA) TERHADAP KADAR GLUKOSA DARAH MENCIT (MUS MUSCULUS) - PUJI LESTARI, NIHAYAH Puji; Tjandrakirana, Tjandrakirana (LenteraBio: Berkala Ilmiah Biologi, 2013)
The main symptom of  diabetes mellitus is an increase of blood glucose concentration, therefore it can be decreased using natural substances. The research aimed to the combination of Caesalpania sappan  L wood and Aloe vera leaves liquids can decrease the concentration  of blood glucose in Mus musculus. This research used  pre-post-test design with RAL. The subjects were 24 Mus musculus of BALB/cAnN strain. The chemical subtance used to increase the concentration  of blood glucose was 1 cc/kgBB of dextrose monohydrate 5 %. The animals were devided into 6 groups that are threated by giving: 1) aquades (KK); 2) Caesalpania sappan L wood liquid  100% (KP1); 3) Aloe vera leaves liquid 100%  (KP2); 4) combination  of Caesalpania sappan L wood and Aloe vera leaves liquid 20% (KP3); 5) combination of Caesalpania sappan L wood and Aloe vera leaves liquid 40% (KP4); 6) combination  of Caesalpania sappan L wood and Aloe vera leaves liquid  60% (KP5). The concentration  of blood glucose was measured using glico test. The data gained were analyzed using T test and One-Way ANOVA at 5% of level test. After giving dextrose monohydrate the glucose concentration of all samples was 160,75 mg/dl.The results of this research shows that the decrease of glucose concentration of   KP1 was 123,75 mg/dl; KP2 was 120,25 mg/dl; KP3 was  118,5 mg/dl; KP4 was 115,75 mg/dl; and  KP5 was 109,75 mg/dl. The analysis result revealed that combination of  Caesalpania sappan L wood and Aloe vera leaves liquids can decrease of the concentration  of blood glucose in  Mus musculus (Fcount (3,499) > Ftable (1,83) with sig value < 0,05) and (tcount (10,939) > ttable  (1,714)) with sig value  < 0,05) . It can be concluded that the combination of Caesalpania sappan  L wood and Aloe vera leaves liquids can decrease the concentration  of blood glucose in Mus musculus.